1998
DOI: 10.1136/jcp.51.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology diagnosis of malignant lymphoma and reactive lymphoid hyperplasia.

Abstract: Aims-To assess the diagnostic accuracy of lymph node fine needle aspiration (FNA) cytology to distinguish reactive lymphoid hyperplasia from malignant lymphoma, and to evaluate the contribution of ancillary techniques applied to cytological material. Methods-Two hundred and seventy seven consecutive lymph node FNA specimens reported to be consistent with reactive lymphoid hyperplasia (n = 213) or suggestive/diagnostic of malignant lymphoma (n = 64) were reviewed. Follow up data were obtained by case record rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 23 publications
1
63
0
1
Order By: Relevance
“…The FNA specimen with predominantly lymphocytes without salivary epithelium was frequently associated with lowgrade lymphoma on final histological diagnosis in both suspicious and malignant cytological diagnosis so it should prompt further study for lymphoma (Cohen et al, 2004). FNA cytology along with various ancillary studies, such as immunocytochemistry and flow cytometry can be helpful to diagnostic and classification lymphomas and separate them from reactive hyperplasia (Stewart et al, 1998;Dong et al, 2001). One adenocarcinoma case was misdiagnosed as negative for malignancy.…”
Section: Discussionmentioning
confidence: 98%
“…The FNA specimen with predominantly lymphocytes without salivary epithelium was frequently associated with lowgrade lymphoma on final histological diagnosis in both suspicious and malignant cytological diagnosis so it should prompt further study for lymphoma (Cohen et al, 2004). FNA cytology along with various ancillary studies, such as immunocytochemistry and flow cytometry can be helpful to diagnostic and classification lymphomas and separate them from reactive hyperplasia (Stewart et al, 1998;Dong et al, 2001). One adenocarcinoma case was misdiagnosed as negative for malignancy.…”
Section: Discussionmentioning
confidence: 98%
“…[7] Early reports suggested that FNA produced high false negative rates in patients with Hodgkin's disease and low grade nonHodgkin's lymphoma. 8 We are presenting our experience with 555 cases of lymphadenopathy gathered over a period of one year. The pattern of benign lesion seen in our study consists of reactive hyperplasia, tuberculous lymphadenitis, acute lymphadenitis and malignant lesion includes metastatic carcinoma and malignant lymphoma/leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Similar mistakes have also been reported and care should be given to the improvement of skills regarding cellular appreciation of malignancy. Immunocytochemistry in this set-up is unique regarding the distinction of neoplastic and activated lymphocytes [24,25]. …”
Section: Discussionmentioning
confidence: 99%